Change in insecticide use behaviors and health effects of commercial vegetable growers: a 10 year follow-up - คำมณีจันทร์ พัฒนศักดิ์; สาหลำ มารีแย (Disease Control Journal, 2018)
Pesticide poisoning is a major health problem in Thailand, especially in commercial agricultural sector. A comparative study is aimed to assess change of insecticide use behaviors and health effects of commercial vegetable and field crops growers. Study subjects were 45 commercial vegetable and field crops growers in Khok Pho District, Pattani. Data were gathered by using interviewing form, blood screening test by using cholinesterase reactive paper and reviewing medical records. According to a 10 years follow-up, two times of data collection had been firstly done in April 2006 and then in April 2016. Data were analyzed by using descriptive statistics, Chi-square test and McNemar test when appropriate. Study results showed that, of a comparative data between 2006 and 2016, application of Methomyl was decline (p=0.007) while that of Carbofuran was increase (p<0.001). Other reactive ingredients, for example, Chlorpyrifos, Malathion, Cypermethrin and Beta-cyfluthrin were not changed in use (p>0.999). While using excess doses of insecticide decreased (p<0.005), dramatically increased in using multi-insecticides mixture (p<0.05). A decline in unsafe disposal of insecticide containers was observed (p<0.005). For health effects, there were decreasing in acute severe insecticide poisoning, dizziness and giddiness, and dry throat (p<0.01). Other insecticide-related symptoms were still presented, but not significantly different between 2006 and 2016. In conclusion, insecticide use behaviors and related-health effects of agricultures had been changed by types of crops that were grown. The farmers had more concern about protecting their crops than their health.